2014
DOI: 10.1093/aje/kwu246
|View full text |Cite
|
Sign up to set email alerts
|

Partnering in Research: A National Research Trial Exemplifying Effective Collaboration With American Indian Nations and the Indian Health Service

Abstract: Despite the fact that numerous major public health problems have plagued American Indian communities for generations, American Indian participation in health research traditionally has been sporadic in many parts of the United States. In 2002, the University of Oklahoma Health Sciences Center (Oklahoma City, Oklahoma) and 5 Oklahoma American Indian research review boards (Oklahoma City Area Indian Health Service, Absentee Shawnee Tribe, Cherokee Nation, Chickasaw Nation, and Choctaw Nation) agreed to participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…We identified one study that was conducted among youth with diagnosed T2D. This study used CER to concentrate on American Indian youth participation in the NIH-funded Treatment Options for Type 2 Diabetes in Adolescents and Youth (TODAY) study, which aimed to determine optimal treatment in youth who were newly diagnosed [24]. Academic researchers partnered with the Oklahoma City Area Indian Health Services and several Oklahoma tribes and nations.…”
Section: Description Of Studies Using Cer In Pediatric Diabetesmentioning
confidence: 99%
“…We identified one study that was conducted among youth with diagnosed T2D. This study used CER to concentrate on American Indian youth participation in the NIH-funded Treatment Options for Type 2 Diabetes in Adolescents and Youth (TODAY) study, which aimed to determine optimal treatment in youth who were newly diagnosed [24]. Academic researchers partnered with the Oklahoma City Area Indian Health Services and several Oklahoma tribes and nations.…”
Section: Description Of Studies Using Cer In Pediatric Diabetesmentioning
confidence: 99%
“…Nine of the articles in this analysis included descriptions of a system or procedure for regulating research and a tribal IRB or tribal community-level review was not available (Table 2). Tribal IRBs or a tribal community-level review of research can provide an expansion on the Common Rule that includes requirements for review and approval of all publications and presentations resulting from the research (Chadwick et al 2014; Angal et al 2016) A tribal community-level review in health research is an acknowledgement of an AIAN groups’ sovereign right to oversee research to protect tribal citizens from individual and/or group harm, (Hull and Wilson 2017) and provides a way for AIAN communities to stay informed of research results and dissemination activities (Angal et al 2016). It should be noted that five of the six articles including an urban sample did not provide a description of a system or procedure for regulating research and a tribal IRB or tribal community-level research review was either not available or not reported as being sought (Orians et al 2004; Legaspi and Orr 2007; Fleischhacker et al 2011; Fleischhacker et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Tribal IRBs, other forms of research review committees, and written policies to oversee research activities are approaches that some tribal communities are adopting to exert sovereign authority over research (Chadwick et al 2014). These AIAN-governed bodies may be charged not only with protecting individual research participants but also the tribal community as a whole, ensuring that potential benefits are not negated by inappropriately conducted research (Morton et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Active and honest relationships that included Native American leadership in research provided successful outcomes to a collaboration between academia and Native American communities. This collaboration also resulted in a position specific for assistance of research facilitation within the Native American community [13]. Literature reviews and meta-analyses can provide deep insight and direct recommendations that nations and communities can move forward on, without hesitation.…”
Section: Recommendationsmentioning
confidence: 98%